2013
DOI: 10.1002/ijc.27996
|View full text |Cite
|
Sign up to set email alerts
|

The significance of TNFAIP8 in prostate cancer response to radiation and docetaxel and disease recurrence

Abstract: TNFAIP8 is a NF-κB-inducible, oncogenic molecule. Previous “promoter array” studies have identified differential methylation and regulation of TNFAIP8 in prostate epithelial and cancer cell lines. Here we demonstrate that TNFAIP8 expression is induced by androgen in hormone-responsive LNCaP prostate cancer cells. In athymic mice bearing hormone-refractory PC-3 prostate tumor xenografts, intravenous treatment with a liposomal formulation of TNFAIP8 antisense oligonucleotide (LE-AS5) caused reduced expression of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
62
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(65 citation statements)
references
References 39 publications
3
62
0
Order By: Relevance
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among TNFAIP8 variants. In order to determine the expression patterns of the variants in human tumors compared with normal tissue, we analyzed cataloged RNA-sequencing (RNA-seq) data from primary human tumor and normal tissue for 11 cancer types in The Cancer Genome Atlas (TCGA) (Figure 1a and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…The last exon is common, whereas usage of other exons differs across variants (Supplementary Figure S1). Several reports have shown that TNFAIP8 is overexpressed in human cancers, [3][4][5]8,[19][20][21][22] yet none of these publications have used methods with adequate specificity to discriminate among TNFAIP8 variants. In order to determine the expression patterns of the variants in human tumors compared with normal tissue, we analyzed cataloged RNA-sequencing (RNA-seq) data from primary human tumor and normal tissue for 11 cancer types in The Cancer Genome Atlas (TCGA) (Figure 1a and Supplementary Figure S2A).…”
Section: Resultsmentioning
confidence: 99%
“…Of interest, TNFAIP8 has been proposed to be a scaffolding protein, and both p53 and PCNA were previously identified as potential TNFAIP8-binding partners. 4 It is thus intriguing to consider the possibility that v2 binding may possibly regulate access of acetylases and/or deacetylases to p53. TNFAIP8 could also conceivably regulate the activity of a signaling protein or transcription factor (other than p53 (Figure 5e)) that regulates PCNA expression.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations